PENERAPAN MODEL PEMBELAJARAN SEARCH SOLVE CREATE SHARE (SSCS) UNTUK MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA KELAS VII-2 SMP NEGERI 13 PEKANBARU - Maida Deli (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2015)
This study aims to improve students' motivation in mathematics for grade VII-2 SMP 13 Pekanbaru through the application of learning models of Search Solve Create Share (SSCS). Subjects in this study were students of grade VII-2 SMP 13 Pekanbaru in academic year of 2013/2014, and the number of students as much as 36 people. While the object of this research is the application of learning models of Search Solve Create Share (SSCS) to increase students' motivation to learn mathematics for grade VII-2 SMP 13 Pekanbaru. This research was conducted in two cycles. The first cycle consists of two meetings and the second cycle consists of three meetings. In order to study this class action work well without the barriers that interfere with the research, researchers compiled stages traversed in action research, namely: planning/ preparation of action, action, observation and reflection. Based on the research results, itcould be concluded that this study could improve students' motivation to learn mathematics for grade VII-2 SMP 13 Pekanbaru. The average student motivation classically at the meeting before the action was 35.3%, whereas in the first cycle average increase student motivation to learn mathematics to 45.7%; and the second cycle increased to 71.8%. From these, the application of learning models of Search Solve Create Share (SSCS) can increase students' motivation to learn mathematics for grade VII-2 SMP 13 Pekanbaru.